A case of rheumatoid pericarditis with high concentrations of interleukin-6 in pericardial fluid. Issue 6 (1st June 2000) - Shikama, N; Terano, T; Hirai, A
Abstract : A case of rheumatoid pericarditis that developed into cardiac tamponade without deterioration of rheumatoid arthritis is described. The concentration of interleukin-6 (IL-6) in pericardial fluid was notably increased compared with serum. IL-6 may be associated with progression or maintenance of rheumatoid pericarditis.